Abundances of Virus-like particles (VLP) resulted in a mesocosm experiment performed in Lake Limnopolar - González, Antonio Camacho (GBIF-Spain, 2013)
This data are part of the activities for the accurate description of the limnetic systems in Byers Peninsula (Livingston Island), considered one of the most important freshwater zones in the Maritime Antarctica.Data are the abundances of Virus-like particles at different experimental conditions of a mesocosm assay performed in the Lake Limnopolar with the aim to evaluate the role of both biotic and abiotic interactions in the pelagic community